Analisis Keoptimalan Fungsi Baitul Maal Pada Lembaga Keuangan Mikro Islam (Studi Kasus Pada BMT Nurul Jannah di Gresik dan BMT Muda di Surabaya) - Rana Ayu Azizah; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Basically Baitul Maal wa tamwil (BMT) have to run optimally both their business functions (Baitul tamwil) and social functions (Baitul Maal). Optimal can be seen from how the organization runs their operations effectively and efficiently. The aim of this research was to determine what causes of less-optimal from the social functions (Baitul Maal) on BMT.This research used qualitative approach and case study method with explanatory study. The informants in this research were managers and administrators of BMT. Based on that method, the selected informants were executive manager of BMT, menager of Baitul Maal, and management of BMT. Data collected by interviews with informants using validation method of sources and data triangulation.The results of this research indicate that their motivation cause disoptimal Baitul Maal function at Islamic microfinance institutions (case study at BMT Nurul Jannah Gresik and BMT Muda Surabaya). REFERENCES Abdullah, Ma’ruf. 2012. Manajemen Berbasis Syariah. Yogyakarta: Aswaja Pressindo.Agoes, Sukrisno. 2013. Auditing: Petunjuk Pemeriksaan Akuntan oleh Akuntan Publik. Jakarta: Salemba Empat.Al-Qur’an Al-Karim. Terjemahan. Departemen Agama IslamBeekun, Rafik Issa. 2006. Strategic Planning and Implementation For Islamic Organizations. USA: The International Institute of Islamic ThoughtBuchari, Nur S. 2009. Koperasi Syariah. Sidoarjo: Masmedia Buana PustakaDaft, Richard L. 2001. Essential of Organozation Theory & Design. Edisi Kedua. South-Western: Thomson LearningDiola, Alfa. 2011. Peran Baitul Maal Wat Tamwil Dalam Peningkatan Kesejahteraan Anggota Pada BMT-UGT Sidogiri di Kota Surabaya. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Griffin, Ricky W. 2013. Management Principles and Practice. Edisi Kesebelas. South-Western: Cengage LearningGrunbaum, Niels N. 2007. Identification of Ambiguity in the Case Study Research Typology: What is a Unit of Analisis.Qualitative Market Research: An International Journal Vol. 10 No.1 pp 79-97. DOI 10.1108/13522750710720413Handoko, T. Hani. 2003. Manajemen. Cetakan Kedelapanbelas. BPFEYogyakarta: Yogyakarta.Huda, Nurul, Achmad aliyadin, Agus Suprayogi, dkk. 2012. Keuangan Publik Syariah: Pendekatran Teoritis dan sejarah. Jakarta: Kencana Prenada Media GroupIlmi, Makhalul. 2002. Teori Dan Praktek Mikro Keuangan Syariah: Beberapa Permasalahan dan Alternatif Solusi. Yogyakarta: UII PressKarim, Adiwarman Azwar. 2010. Sejarah Pemikiran Ekonomi Islam. Edisi Ketiga. Jakarta: RajaGrafindo PersadaKurniawan, Agung. 2005. Transformasi Pelayanan Publik. Yogyakarta: Pembaruan.Muhammad. 2007. Lembaga Ekonomi Syariah. Yogyakarta: Graha IlmuNanda, Aditya Surya Nanda. 2012. Keseimbangan Fungsi Baitul Maal Dan Fungsi Baitul Tamwil Pada Lembaga Keuangan Mikro Islam Di Surabaya Dan Sekitarnya. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi Dan Bisnis Universitas Airlangga Ridwan, Muhammad. 2004. Manajemen Baitul Maal Wat Tamwil (BMT). Yogyakarta: UII PressRivai, Veithzal. 2009. Islamic Human Capital Dari Teori Ke PraktikManajemen Sumber Daya Islami. Edisi Pertama. Jakarta: Rajawali Pers.Robbins, Stephen P. 2003. Organizational Behaviour. Teenth Edition. New Jersey: Prentice.Sudarsono, Heri. 2012. Bank dan Lembaga Keuangan Syariah: Deskripsi dan Ilustrasi. Edisi Ketiga. Yogyakarta: Ekonisia UII YogyakartaYin. Prof. Dr. Robert K. 2013. Study Kasus Desain & Metode.Cetakan Kedua Belas. Edisi Pertama. Jakarta: RajaGrafindo Persada (Rajawali).